The Consequences of Inequality: Beliefs and Redistributive Preferences - Max Lobeck; Morten Nyborg Støstad (Center for Economic Studies and ifo Institute (CESifo), 2023)
What matters for individuals' preferences for redistribution? In this paper we show that consequentialist beliefs about inequality — beliefs about how economic inequality changes the crime rate or the quality of democratic institutions, for example — have a large causal impact on individuals' redistributive preferences. Using two representative surveys of a combined 6,731 U.S. citizens, we show that a majority of respondents believe that inequality leads to a wide range of negative societal outcomes. We establish a causal link from such beliefs to individuals' redistributive preferences by using exogenously provided video information treatments. With this and other methods we show that inequality externality beliefs impact redistributive preferences on the same order of magnitude as broad economic fairness views. These inequality externality beliefs are relatively equally held across political affiliations as well as incomes. We discuss whether a focus on inequality's consequences could shape a distinct conversation about redistribution.
Keywords: C83; C90; D63; H20; 330; inequality; inequality externalities; surveys; redistribution